Primary Esophageal Tuberculosis Without Dysphagia or Odynophagia in a Patient Without HIV - Ogbomo, Henry (ACG Case Rep J, 2020)
We report a case of primary esophageal tuberculosis in a 35-year-old woman without HIV who presented with a month's history of epigastric and chest pain without dysphagia or odynophagia and was found to have histologic evidence of multiple caseating granulomata on esophageal biopsy, which was confirmed positive for Mycobacterium tuberculosis complex DNA and cultures.